Enhancing racking stiffness in tall timber buildings using double-skin façades - Kozem Šilih, Erika (Advances in production engineering and management, 2025)
The main goal of the paper is to present possible benefits in application of previously developed innovative in-plane load-bearing timber double-skin façade elements (DSF) as additional bracing elements in tall timber buildings. Therefore, a six-storey prefabricated timber structure of a height of 15 m and with a regular floor-plan is analysed by a seismic excitation of ag = 0.225 · g with a strong asymmetrical position of transparent façade elements. Two structural solutions are analysed: a hybrid system combining CLT and Light Timber-Framed walls and a non-hybrid structure made entirely of CLT. In both cases, DSF elements are first considered non-resisting and later as racking-resisting bracing elements. Numerical results show that using racking-resisting DSF elements in a hybrid system (CLT+LTF) achieves a similar increase in overall racking stiffness as a non-hybrid CLT structure with non-resisting DSF. Previous studies highlight hybrid timber systems as the preferred approach due to structural, energy-efficient, and ecological advantages. This finding is significant, offering practical benefits and new design opportunities for modern tall timber buildings with asymmetrical transparent façades, improving both energy efficiency and interior illumination in contemporary prefabricated structures.
Keywords: double-skin façades; dvoslojne fasade; glass; les; lesene konstrukcije; matematično modeliranje; mathematical modelling; numerična preiskava; potresna odpornost; racking resistance; seismic design; seizmično načrtovanje; steklo; tall timber buildings; timber; togost; visoke lesene stavbe